TCP-friendliness of rate-based congestion control protocols - Hassan, Suhaidi (2003)
The main purpose of rate-based TCP-friendly congestion control protocols is to ensure that the application's traffic shares the network in a fairly and friendly manner with the dominant TCP traffic.In this work, we compare the performance of two rate-based TCP-friendly congestion control protocols, namely the rate adaptation protocol (RAP) and TCP-friendly rate control protocol (TFRC). Our experimental results reveal that the equation-based TFRC is able to achieve throughput that is close to the throughput of a TCP connection using the same network path under the same network conditions.Also, the results demonstrate that the TFRC is friendlier and robust in most of our experiments, as compared to RAP.